2018
DOI: 10.5032/jae.2018.04194
|View full text |Cite
|
Sign up to set email alerts
|

Using Cognitive Dissonance to Theoretically Explain Water Conservation Intentions

Abstract: Water is a scarce resource in Florida. There is an immediate need to reduce the stress on water resources and make the availability of water more sustainable by encouraging engagement in water conservation among the residents of Florida. This study examined how the future intentions of high water users in Florida] to conserve water outdoors were influenced by cognitively dissonant attitudes and behaviors. The independent variables used in the study were: government trust, current water conservation practices, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In this regard, Kagawa states that "[t]here are multiple factors which influence the process of behavioral change and further investigation of dissonance between students' perception of sustainability and their individual actions needs to be explored" [106]. See, for example, research on the attitude-behavior gap [103,107,108] or cognitive dissonance [109,110]. Further implications for future research and an outlook will be given in the concluding section of this article.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Kagawa states that "[t]here are multiple factors which influence the process of behavioral change and further investigation of dissonance between students' perception of sustainability and their individual actions needs to be explored" [106]. See, for example, research on the attitude-behavior gap [103,107,108] or cognitive dissonance [109,110]. Further implications for future research and an outlook will be given in the concluding section of this article.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research (Chaudhary et al, 2018;Larson et al, 2011) has found a significant negative relationship between conservative political orientation and private-sphere water conservation behaviors. The findings of this study are consistent with these previous studies and extend this relationship into public-sphere water conservation behaviors; however, the observed correlation was low (Davis, 1973) and political orientation did not enter into the regression equation.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 91%
“…Older adults, females, persons living in single-family residences, and those holding more liberal political orientations are more likely to engage in private-sphere water conservation behaviors (Arnocky & Stroink, 2011;Chaudhary et al, 2018;Clark & Finley, 2007;Larson et al, 2011). Individuals with higher levels of education (Larson & Larch, 2010) and those with college majors in natural resources (Arnocky & Stroink, 2011) are more likely to engage in broader proenvironmental public-sphere behaviors.…”
Section: Introduction and Problem Statementmentioning
confidence: 99%
“…Communication research regularly accepts and uses non‐probability opt‐in sampling as a sampling method (Lamm and Lamm 2019). For example, Chaudhary et al (2018) used non‐probability opt‐in sampling to collect data on high‐level water users to understand their lack of interest in conserving water. However, one limitation of this study is that non‐probability opt‐in sampling may result in a biased sample because not all types of individuals have access to the internet and not all types of individuals will answer surveys (Lamm and Lamm 2019).…”
Section: Methodsmentioning
confidence: 99%